STUDY OF LIQUEFACTION POTENTIAL INDUCED GROUND SETTLEMENT AND LATERAL SPREADING IN LOWER CIMANUK CATCHMENT AREA, INDRAMAYU REGENCY, WEST JAVA PROVINCE - Asrul Sani, Rifki
Indramayu District and its surrounding area dominated by Quartenary sediment composed by fluvial, flood plain, beach ridge and deltaic sediments. That area is nearer from active faults, The Baribis-Subang fault segment with 6.5 Mw that potentially liquified. Research in lower catchment Cimanuk area Indramayu Regency, West Java Province aims to determine mechanical and physical of Quarternary sediment, liquefaction potential induced ground settlement and lateral spreading. The methods used in this study are 4 core observation and cone penetration patterns (10 CPTu and 13 CPT) and laboratory analysis such as density, grain size, Atterberg limits and sediment classification. Liquefaction potential analysis used with 6.5 Mw earthquakes by considering four different PGA value such as 0.15 g, 0.3 g, FA median PGA and estimated PGA. Safety factor against liquefaction (FSL) may reflected liquefaction potential induced ground settlement and lateral spreading. Based on core observation, cone penetration pattern and laboratory analysis, there are three facies that develop at the research area such as delta plain facies composed of fluvial sand, silt and clay, delta front facies composed of beach ridge sands and sandy silt, and the last is prodelta facies which composed of silt and clay. Generally, sands (fluvial and beach ridge sands facies) and sandy sediment (sandy silt delta front facies) at the research area are potentially liquefied especially at northern research area, it’s caused by N-SPT value less than 10 or cone resistance value (qc) less than 6,000 kPa. Liquefaction potential analysis induced ground settlement and lateral spreading shows that FA median PGA is the highest value among all. Generally, the research area is classified as medium damage according ground settlement value with considering different PGA.